Philippine agenda ([Quezon City GMA News and Public Affairs, 2007)
The five pillars of GMA news and public affairs, Mike Enriquez, Mel Tiangco, Jessica Soho, Arnold Clavio and Vicky Morales join forces in the groundbreaking pre-election series Philippine agenda. Combining the efforts GMA Networks multi-awarded news and public affairs teams, Philippine Agenda presents the country's biggest issues, education, health, corruption, housing, labor, hunger, crime and justice, and electoral reform with the objective of calling viewers to action.
Edukasyon / ni Jessica Soho -- Kalusugan / ni Arnold Clavio -- Katiwalian / ni Mike Enriquez -- Pamahay / ni Mel Tiangco -- Trabaho / ni Vicky Morales -- Gutom / ni Mike Enriquez -- Krimen at hustisya / ni Arnold Clavio -- Reporma sa eleksyon / ni Jessica Soho.
Summary taken from container.
Not viewed.
Sources used: DVD container; cataloging record from OvOp field office.
In Tagalog.
Keywords: Philippines -- Politics and government -- 21st century; Nonfiction television programs